(untitled) (Revista Educação, Artes e Inclusão, 2025)
The theme of this research is the visual arts book, the book as a know-object, aesthetic and artistic. The focus is on the elaboration of the art books with visual art themes from Santa Catarina, because in the last years, investigating Blumenau Art Museum (Museu de Arte de Blumenau – MAB), it has been acknowledged the fragility of the original art materials. The objective is to comprehend the relations between the images and the words that can be used on children’s art books elaboration process that aims the aesthetic formation in cultural mediation processes. It is presented a book proposal based on the work “Como fazer um pote” from the Artist Roseli Moreira. The art book for children elaboration is based on a few aspects: the meeting with a local artist; the material exploration; the contact of the reader with the work of art; the concepts of the relational art present on the chosen work; the choice of an accessible source - all challenges to the book creation process.